Preparation method of wear-resistant coating of wind power bearing
Through high-frequency electromagnetic induction preheating and solid-state deposition of coating particles, the problem of insufficient binding force of wind power bearing coatings is solved, significantly improving the wear resistance and service life of the coating, while reducing production costs.
Patent Information
- Application Number
- CN202411855950.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, conventional metal solid deposits on wind power bearings have insufficient binding force and poor wear resistance, which cannot meet the use requirements of wind power bearings.
High-frequency electromagnetic induction is used to preheat the deposited area of the wind power bearing and solid-state deposition of coating particles, and alloy powder or Ni-based doped WC cermet is used as coating particles.
It greatly improves the interface bonding strength of the metal deposited body, extends the service life of wind power bearings, and reduces production costs, avoiding the oxidation problems caused by laser preheating and nozzle blocking.
Smart Images

Figure CN119663269A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating preparation, and in particular to a method for preparing a wear-resistant coating of a wind power bearing. Background Art
[0002] Wind turbine bearings are a special type of sliding bearings that are used in harsh environments and have high maintenance costs. Therefore, wind turbine bearings are required to have a long service life when they are prepared. Therefore, it is necessary to prepare a strengthening coating for wind turbine bearings during preparation to improve the performance of wind turbine bearings and extend their service life. The coating formation methods commonly used in the prior art include metal solid deposition. Metal solid deposition uses compressed gas (nitrogen, helium, air or mixed gas, etc.) as an accelerating medium to carry metal solid particles into the Laval nozzle to produce a supersonic gas-solid two-phase flow. When the metal solid particles collide with the substrate surface at a high speed (greater than or equal to its critical deposition speed), the metal particles and the substrate surface material will undergo strong plastic deformation, and a large number of mechanical bites and micro-area metallurgical bonds will form at the material interface. After a large number of metal particles collide and deposit, a metal deposit will be formed on the substrate surface.
[0003] However, the coating formed on the wind turbine bearing by conventional metal solid deposition cannot meet the use requirements of the wind turbine bearing, that is, the coating formed by conventional spraying has insufficient bonding strength with the wind turbine bearing substrate and poor wear resistance.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a wear-resistant coating of a wind turbine bearing. The embodiment of the present invention provides a method for preparing a wear-resistant coating of a wind turbine bearing, which greatly improves the interface bonding strength of a metal deposit.
[0006] The present invention is achieved in that:
[0007] The present invention provides a method for preparing a wind power bearing wear-resistant coating, comprising: preheating a to-be-deposited area of a substrate by high-frequency electromagnetic induction, and depositing coating particles in a solid state.
[0008] In an optional embodiment, the preheating temperature is lower than the melting point of the wind power bearing;
[0009] Preferably 100-1000°C;
[0010] Preferably, the thermal impact on the surface of the substrate after preheating is less than 50 μm.
[0011] In an optional embodiment, the coating particles are selected from alloy powders or Ni-based doped WC cermets.
[0012] In an alternative embodiment, the alloy powder includes copper, aluminum and iron;
[0013] Preferably, the alloy powder comprises 80-90% copper, 8-15% aluminum and 1-5% iron in terms of mass percentage.
[0014] In an optional embodiment, the Ni-based doped WC cermet includes 60-80% nickel and 20-40% WC in mass percentage.
[0015] In an optional implementation, the conditions of high-frequency electromagnetic induction include: voltage AC 350-400V, power 2-200KW, and operating frequency>150KHz.
[0016] In an optional embodiment, the speed of solid-state deposition of the coating particles is >500 m / s, and the deposition temperature is less than the melting point of the coating particles themselves; preferably, the deposition temperature is 25-180°C.
[0017] In an alternative embodiment, preheating and solid-state deposition are performed simultaneously.
[0018] In an optional embodiment, preheating is performed before solid-state deposition.
[0019] In an alternative embodiment, solid-state depositing the coating particles is deposited only once;
[0020] The coating particles are solid-deposited to form a thick coating; the thickness of the thick coating is greater than 1.5 mm.
[0021] In an optional embodiment, the preheating step further includes heating a side of the substrate opposite to a side where the coating particles are solid-state deposited.
[0022] The present invention has the following beneficial effects: the embodiment of the present invention uses high-frequency electromagnetic induction to preheat the area to be deposited on the substrate, which can not only greatly improve the interfacial bonding strength of the metal deposit; at the same time, the preheating time is short, the thermal impact on the substrate is small, it is highly efficient and energy-saving, and the thermal efficiency is as high as 90% or more; it is completely suitable for the deposition of high laser reflective metals and alloys such as gold, silver, copper, aluminum, and platinum. At the same time, compared with laser preheating, this method eliminates the thermal impact of laser reflection on other components of solid-state deposition equipment and avoids the gun blocking phenomenon caused by nozzle heating; it is simple to operate, has a low failure rate, greatly reduces production costs, and saves resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 The present invention provides the morphology of the spray deposited body of Example 1 and Comparative Example 1, wherein the left side is Example 1 and the right side is Comparative Example 1;
[0025] Figure 2 This is the metallographic structure of the spray deposited body of Example 1 of the present invention;
[0026] Figure 3 This is the metallographic structure of the spray deposited body of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0028] The existing technology often uses solid deposition to form a coating, but the inventors found that conventional cold spray solid deposition has little effect on wind turbine bearings, so they improved it, such as heating the substrate and then cold spraying. However, the high-power energy and reflection of laser heating will cause thermal effects on the solid deposition device, which will affect the effect of subsequent cold spraying. At the same time, the cold spray nozzle is also prone to gun blocking due to temperature rise. Laser preheating is prone to substrate oxidation, which will affect the performance of wind turbine bearings.
[0029] Based on the above technical problems, an embodiment of the present invention provides a method for preparing a wear-resistant coating of a wind turbine bearing, comprising: preheating the area to be deposited on the substrate by high-frequency electromagnetic induction, and solid-state depositing coating particles.
[0030] Specifically, before the coating is prepared, high-frequency electromagnetic induction is used to generate numerous small eddy currents in the substrate area to be deposited, so as to preheat the substrate. The preheating temperature is lower than the melting point of the wind turbine bearing, for example, 100-1000°C; after preheating, the thermal impact on the surface of the substrate is less than 50μm.
[0031] Among them, the conditions of high-frequency electromagnetic induction include: voltage AC 350-400V, power 2-200KW, working frequency>150KHz, so that the current is concentrated on the substrate surface to enhance the surface preheating effect.
[0032] At the same time, the preheating temperature is controlled by the temperature control mode. Specifically, the surface temperature of the substrate is monitored by the temperature detection control system and fed back to the electromagnetic induction heating system. The electromagnetic induction heating system adjusts the surface temperature of the substrate by adjusting the power of the electromagnetic induction heating system according to the temperature feedback from the temperature monitoring system and the required preheating temperature value of the substrate surface.
[0033] Next, the coating particles are solid-state deposited. The solid-state deposition can be performed simultaneously with the preheating, or the preheating can be performed first and then the solid-state deposition. In the embodiment of the present invention, it is preferred that the preheating and the solid-state deposition are performed simultaneously to improve the deposition effect.
[0034] The coating particles are selected from alloy powder or Ni-based doped WC cermet.
[0035] The alloy powder comprises copper, aluminum and iron, and specifically comprises 80-90% copper, 8-15% aluminum and 1-5% iron.
[0036] For example, the copper content is 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89% and 90%, etc., any value between 80-90%, or a range value between any two values.
[0037] The aluminum content is 8%, 9%, 10%, 11%, 12%, 13%, 14% and 15%, etc., any value between 8-15%, or a range value between any two values.
[0038] The iron content is 1%, 2%, 3%, 4% and 5%, etc., any value between 1-5%, or a range value between any two values.
[0039] The Ni-based doped WC cermet includes 60-80% nickel and 20-40% WC. For example, the nickel content is any value between 60-80% such as 60%, 65%, 70%, 75% and 80%, or a range value between any two values. The WC content is any value between 20-40% such as 20%, 25%, 30%, 35% and 40%, or a range value between any two values.
[0040] The embodiments of the present invention use the above particles to effectively form a coating, thereby improving the bonding strength between the coating and the wind turbine bearing and extending the service life of the wind turbine bearing.
[0041] The speed of solid-state deposition of the coating particles is >500 m / s, and the deposition temperature is less than the melting point of the coating particles themselves; preferably, the deposition temperature is 25-180°C.
[0042] The embodiment of the present invention can obtain a thick coating by only one solid deposition, and the thickness of the thick coating is greater than 1.5 mm. In the prior art, to prepare a coating of this thickness, multiple spraying is generally required, but the method provided by the embodiment of the present invention can obtain a thick coating by only one spraying, and the coating has good bonding strength with the substrate.
[0043] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0044] Example 1
[0045] An embodiment of the present invention provides a method for preparing a wear-resistant coating of a wind turbine bearing, the preparation method comprising:
[0046] S1. Prepare coating particles by mixing Cu, Al and Fe metals in proportions of 88%, 10% and 2%.
[0047] S2, high frequency electromagnetic induction assisted cold spraying to prepare coating;
[0048] Specifically, the substrate to be deposited is preheated by high-frequency electromagnetic induction, and the conditions of high-frequency electromagnetic induction are set as follows: power supply voltage AC 380V, power 3KW, operating frequency 160KHz. The substrate preheating temperature is 500°C, and the thermal impact of the substrate surface is strictly controlled within 30μm.
[0049] At the same time, solid-state deposition of coating particles was performed. The distance between the solid-state deposition nozzle and the electromagnetic induction heater was 25 mm. The speed of solid-state deposition of metal particles was 800 m / s and the temperature was 160° C. The above solid-state deposition was performed only once, and the thickness of the obtained coating was 1.6 mm.
[0050] Example 2
[0051] An embodiment of the present invention provides a method for preparing a wear-resistant coating of a wind turbine bearing, the preparation method comprising:
[0052] S1. Prepare coating particles by mixing nickel and WC in a ratio of 60% and 40%.
[0053] S2, high frequency electromagnetic induction assisted cold spraying to prepare coating;
[0054] Specifically, the substrate to be deposited is preheated by high-frequency electromagnetic induction, and the conditions of high-frequency electromagnetic induction are set as follows: power supply voltage AC 380V, power 5KW, working 180KHz. The substrate preheating temperature is 450°C, and the thermal impact of the substrate surface is strictly controlled within 30μm.
[0055] At the same time, solid-state deposition of coating particles was performed. The distance between the solid-state deposition nozzle and the electromagnetic induction heater was 28 mm. The speed of solid-state deposition of metal particles was 1000 m / s and the temperature was 150° C. The above solid-state deposition was performed only once, and the thickness of the obtained coating was 1.6 mm.
[0056] Example 3
[0057] An embodiment of the present invention provides a method for preparing a wear-resistant coating of a wind turbine bearing, the preparation method comprising:
[0058] S1. Prepare coating particles by mixing nickel and WC in a ratio of 80% and 20%.
[0059] S2, high frequency electromagnetic induction assisted cold spraying to prepare coating;
[0060] Specifically, the substrate to be deposited is preheated by high-frequency electromagnetic induction, and the conditions of high-frequency electromagnetic induction are set as follows: power supply voltage AC 350V, power 200KW, working 200KHz. The substrate preheating temperature is 100°C, and the substrate surface thermal impact is strictly controlled within 40μm.
[0061] At the same time, solid-state deposition of coating particles was performed. The distance between the solid-state deposition nozzle and the electromagnetic induction heater was 20 mm. The solid-state deposition of metal particles was performed at a speed of 600 m / s and a temperature of 120° C. The above solid-state deposition was performed only once, and the thickness of the obtained coating was 1.8 mm.
[0062] Example 4
[0063] An embodiment of the present invention provides a method for preparing a wear-resistant coating of a wind turbine bearing, the preparation method comprising:
[0064] S1. Prepare coating particles by mixing Cu, Al and Fe metals in proportions of 80%, 15% and 5%.
[0065] S2, high frequency electromagnetic induction assisted cold spraying to prepare coating;
[0066] Specifically, the substrate to be deposited is preheated by high-frequency electromagnetic induction, and the conditions of high-frequency electromagnetic induction are set as follows: power supply voltage AC 400V, power 2KW, working 170KHz. The substrate preheating temperature is 2500°C, and the thermal impact of the substrate surface is strictly controlled within 10μm.
[0067] At the same time, solid-state deposition of coating particles was performed. The distance between the solid-state deposition nozzle and the electromagnetic induction heater was 18 mm. The speed of solid-state deposition of metal particles was 650 m / s and the temperature was 150° C. The above solid-state deposition was performed only once, and the thickness of the obtained coating was 1.7 mm.
[0068] Comparative Example 1: A coating was prepared by referring to the preparation method of Example 1, except that no preheating was performed and solid-state deposition was performed directly. The conditions of the solid-state deposition were the same as those of Example 1.
[0069] Comparative Example 2: Preheating the substrate with laser and performing solid-state deposition at the same time, the specific process is: firstly heating the entire area to be deposited. The conditions of solid-state deposition are the same as those of Example 1.
[0070] Comparative Example 3: A coating was prepared by referring to the preparation method of Example 1, except that the preheating temperature of the substrate was increased to 1200°C.
[0071] Test Example 1
[0072] The morphology of the spray deposits of Example 1 and Comparative Example 1 is shown in Figure 1. Figure 1 ,in Figure 1 The left side in the middle is the morphology of the spray-deposited body of Example 1, and the right side is the morphology of the spray-deposited body of Comparative Example 1.
[0073] The metallographic structure of the spray deposits of Example 1 and Comparative Example 1 was tested. Figure 2 and Figure 3 .
[0074] according to Figure 1-Figure 3 It can be seen that the deposited body prepared by electromagnetic heating technology has dense structure and high bonding strength, while the deposited body prepared without electromagnetic heating technology is cracked and has no bonding strength. Since the electromagnetic induction heating technology improves the plastic deformation of the matrix material, the mechanical bite force increases when the powder particles hit the matrix.
[0075] Test Example 2
[0076] The coatings prepared in Example 1 and Comparative Examples 1 to 3 were tested for bonding strength with the substrate and porosity, wherein the bonding strength test was conducted in accordance with GB / T 8642, and the porosity test was conducted in accordance with ASTM E2109. The results are shown in the table below.
[0077] name Metallography Porosity Bonding strength Example 1 No cracks <0.5% >60MPa Comparative Example 1 Cracking >2% <26MPa Comparative Example 2 No cracks <1% >55MPa Comparative Example 3 Matrix deformation >2% <20MPa
[0078] According to the above table, the use of electromagnetic induction heating technology can significantly improve the deposit structure and enhance the bonding performance. Although laser technology can still be used to prepare dense and well-bonded deposits, the equipment is often burned under high power conditions, affecting the operation of the equipment. A higher preheating temperature is not only unhelpful to the coating structure and bonding performance, but also causes deformation of the substrate.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a wear-resistant coating for a wind turbine bearing, characterized in that: include: High-frequency electromagnetic induction is used to preheat the area to be deposited on the substrate, and the coating particles are deposited in a solid state.
2. The method for preparing the wear-resistant coating of a wind turbine bearing according to claim 1, characterized in that: The preheating temperature is lower than the melting point of the wind power bearing; Preferably 100-1000°C; Preferably, the thermal impact on the surface of the substrate after preheating is less than 50 μm.
3. The method for preparing the wear-resistant coating of a wind turbine bearing according to claim 1, characterized in that: The coating particles are selected from alloy powder or Ni-based doped WC cermet.
4. The method for preparing the wear-resistant coating of a wind turbine bearing according to claim 3, characterized in that: The alloy powder includes copper, aluminum and iron; Preferably, the alloy powder comprises 80-90% copper, 8-15% aluminum and 1-5% iron in terms of mass percentage.
5. The method for preparing the wear-resistant coating of a wind turbine bearing according to claim 3, characterized in that: In terms of mass percentage, the Ni-based doped WC cermet includes 60-80% nickel and 20-40% WC.
6. The method for preparing a wind turbine bearing wear-resistant coating according to claim 1, characterized in that: The conditions for high-frequency electromagnetic induction include: voltage AC 350-400V, power 2-200KW, operating frequency>150KHz; Preferably, the speed of solid-state deposition of the coating particles is >500 m / s, and the deposition temperature is less than the melting point of the coating particles themselves; preferably, the deposition temperature is 25-180°C.
7. The method for preparing a wind turbine bearing wear-resistant coating according to claim 1, characterized in that: Preheating and solid-state deposition are performed simultaneously.
8. The method for preparing a wind turbine bearing wear-resistant coating according to claim 1, characterized in that: It includes preheating followed by solid-state deposition.
9. The method for preparing a wind turbine bearing wear-resistant coating according to claim 1, characterized in that: Solid-state deposition of the coating particles is deposited only once; The coating particles are solid-deposited to form a thick coating; the thickness of the thick coating is greater than 1.5 mm.
10. The method for preparing a wind turbine bearing wear-resistant coating according to claim 1, characterized in that: Also includes: Preheating is to heat the side of the substrate opposite to the side where the coating particles are solid-state deposited.